2019
DOI: 10.3390/antiox8080284
|View full text |Cite
|
Sign up to set email alerts
|

Poly (α-Dodecyl γ-Glutamate) (PAAG-12) and Polylactic Acid Films Charged with α-Tocopherol and Their Antioxidant Capacity in Food Models

Abstract: Poly (α-dodecyl γ-glutamate) (PAAG-12) was successfully synthesized from poly(γ-glutamic acid) (PGGA) according to Nuclear Magnetic Resonance (NMR) analyses. PAAG-12 films were prepared and enriched with 5% α-tocopherol, with the aim of using them as novel antioxidant active packaging for food applications. Thermogravimetric Analysis (TGA) characterization determined that α-tocopherol improved thermal stability of films, which is beneficial for industrial processing. Polylactic Acid (PLA) films prepared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…In ethanol: water 75:25 medium, a rapid burst stage occurred after 6 minutes in which 85% of the active product was released (Figure 8). This result was similar to that observed by Estevez-Areco et al [45] who reported a rapid release of a Rosemary ethanolic extract contained in PVA fibers obtained by electrospinning. Souza et al [47] also observed a similar result working with polylactic acid nanofibers (PLA) used to encapsulate linalool by synthesizing fibers with varying amounts of terpene, reporting that the amount of linalool on the surface results in the release of more than 80% in just 30 minutes.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
See 1 more Smart Citation
“…In ethanol: water 75:25 medium, a rapid burst stage occurred after 6 minutes in which 85% of the active product was released (Figure 8). This result was similar to that observed by Estevez-Areco et al [45] who reported a rapid release of a Rosemary ethanolic extract contained in PVA fibers obtained by electrospinning. Souza et al [47] also observed a similar result working with polylactic acid nanofibers (PLA) used to encapsulate linalool by synthesizing fibers with varying amounts of terpene, reporting that the amount of linalool on the surface results in the release of more than 80% in just 30 minutes.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
“…At the initial phase, electrospun nanostructures exhibited a marked burst release, and then the curve tended to a plateau or a gradual release. The increase in the ethanol content in the medium caused an increase in the amount of active component released intensifying the burst effect [45], which was demonstrated by the values of the constant K b J o u r n a l P r e -p r o o f (Table 4). This fact may be due to an increase in the affinity of the essential oil for the medium.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 93%
“…A similar dependence between the amount of thymol released and the obtained antioxidant activity was also observed by Ramos et al in PP-based films using thymol and carvacrol as active additives [56]. These results are also in agreement with previous reports dealing with bioactive compounds, such as thymol obtained from essential oils, herbs, or spices, presenting antioxidant capacity and strong protection of food when released from the polymer matrix [57][58][59][60][61][62].…”
Section: Antioxidant Activity Of Active Pla-based Filmssupporting
confidence: 90%
“…Among various natural active additives, α-tocopherol (TOC) is known to be a potent antioxidant agent and films loaded with this antioxidant have been proved to be effective in retarding lipid oxidation [19][20][21]. This natural additive is authorized as food contact material by EFSA and FDA authorities [22], and it can provide antioxidant/antimicrobial properties to the food product while also stabilizing the polymer matrix during processing [12].…”
Section: Introductionmentioning
confidence: 99%